Rekontruksi Paradigma Jual Beli Dalam Hukum Islam Era Kontemporer - Lidiya Putri; Reza Azurma; Putri Dwi Yulisa; Nurainun (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The Qur'an was revealed to be understood and put into practice, its presence is a solution for humans. Some of the verses are quite clear, but some still require explanation, both in terms of buying and selling in business ethics. The concept of buying and selling in Islamic law is a subject of discussion among fiqh scholars who always have different opinions regarding how to deal with it. In this case the author tries to explore the concept of buying and selling transactions in Islamic law both explicitly and implicitly in the broad sense of buying and selling, along with explaining its implementation and extending it to contemporary interpretations which include the characteristics and paradigms that surround it. With the aim of outlining an idea for building or reconstructing paradigms in the current contemporary era due to developments over time.